Learning Patterns, Personality Traits and Motivational Profile of Students of Dual Learning Modality - Cristina Torrelles-Nadal; Georgina París-Mañas; Carla Quesada-Pallares; Jordi Coiduras-Rodríguez (Universidad Pedagógica Nacional, 2020)
The aim of this research article is to identify the profile of students enrolled in dual learning model and standard learning model based on personality traits, learning patterns and motivational orientation. Participants included 212 freshmen enrolled dual learning model (N=97) and standard model (N=115) in the Primary Education Degree. The participants completed 3 questionnaires: (1) Learning Combination Inventory (Johnston & Dainton, 1996), (2) Big-Five Personality Inventory (Bermúdez, 1995), and (3) Motivational Profile Inventory (Corral, Arribas & Fernández, 2010). The results showed that the students who enrolled in dual learning modality tend to be less open, more emotionally stable and take care of their relationships to a greater extent. The two later characteristics are essential for the typology of the learning modality because it is more complex to work and learn in two different environments than one as standard learning. Despite these results, the groups of both learning modalities are similar and therefore possible future lines are considered. Future studies should be conducted with much larger samples and longitudinal design that allows corroborating (or not) that the students who study in dual learning modality are different or can vary their motivational orientations or improve their learning patterns during the course of their training.